MANFAAT TEKNIK RELAKSASI DAN STATUS GIZI TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK USIA 3-5 TAHUN DI PAUD/TK AL-HIKMAH - Fitriahadi, Enny; Lestari, Uti (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2014)
The Benefits of Relaxation Techniques and Nutritional Status Of Gross Motor Development of Children Aged 3-5 Years. Background: The process of growth and development of children is strongly influenced by feeding nutritious food for children. The provision of good nutrition is important, because an unbalanced nutrition or malnutrition and a low level of health will greatly affect the growth and development of children. Malnutrition such as (energy, protein, iron) can cause a variety of limitations horizontal growth (growth faltering), weight and height deviates from normal growth, is also associated with motor developmental delay (Husaini, 2003). Objective: Want to know the benefits of relaxation techniques and nutritional status of the gross motor development of children aged 3-5 years in early childhood / kindergarten Al-Hikmah Village Sidakaya Cilacap. Methods: The research used in this study was an observational analytic method with cross sectional sample of 30 children with a number of criteria that all children in early childhood / kindergarten Al-Hikmah. Results: that the average gross motor development before action is taken is 2.1667 with a standard deviation of 0.37905. While the average gross motor development after the action is 1.1667 with a standard deviation of 0.46113. From the above results obtained P value 0.000 value so it can be concluded that the alpha 5% showed significant benefit in relaxation techniques and nutritional status of the gross motor development age 3-5 years in early childhood / kindergarten Al-Hikmah Cilacap. Key words: The development of gross motor skills, relaxation techniques, nutritional status